A 5-Year Retrospective Review of Avian Diseases Diagnosed at the Department of Pathology, University of Georgia. Issue 2 (August 2016) - Nemeth, N.M.; Gonzalez-Astudillo, V.; Oesterle, P.T.; Howerth, E.W.
Summary: Avian samples ( n  = 827) submitted to the University of Georgia from 2006 to 2011 were reviewed to determine common disease entities and taxa-specific patterns. The study included 153 species, with 64.5% Psittaciformes, 11.3% Passeriformes, 7.9% Galliformes, 3.8% Columbiformes and 3.5% Anseriformes. Infectious agents were identified in 226 birds (27.3%); bacterial infections ( n  = 119; 14.4%) were most commonly gram-negative bacilli and Chlamydia psittaci and less commonly Mycoplasma and Mycobacterium spp. Mycotic infections (e.g. Aspergillus spp., Candida spp.) were identified in 66 birds (7.9%), followed by viruses in 30 birds (3.6%), most commonly polyomavirus and poxviruses. Eighteen birds had macroparasite infections, which were most common in Galliformes and most often involved gastrointestinal Capillaria spp. Neoplasia was diagnosed in 76 birds (9.2%) of 25 species, with 79% of the tumours deemed to be malignant. The most common neoplasm was lymphoma ( n  = 17; 22.4%), which was diagnosed in Psittaciformes, Galliformes and Passeriformes. Adenocarcinoma ( n  = 9) was found most frequently in the reproductive and gastrointestinal tracts. Haematopoietic neoplasms included myelocytoma and erythroid leucosis. Atherosclerosis was most common in psittacines (23/32; 71.8%) and in raptors and aquatic birds. Seventeen birds, mostly psittacines and aquatic birds, had amyloidosis, most often in the liver, kidney and spleen. Twenty-two birds had gout, most commonly the visceral form. Overall, bacterial infection was the most frequently diagnosed cause of death in captive birds, most commonly in Psittaciformes, followed by Passeriformes and Galliformes. Neoplasia was most common in Psittaciformes, which generally are longer lived than other taxa studied. Some disease entities (e.g. atherosclerosis and aspergillosis) may be associated with captive conditions, and some may involve a genetic predisposition (e.g. atherosclerosis, amyloidosis and haemosiderosis).